Prevalence of cardiomyopathy in apparently healthy cats - Chin, Meixin (2018)
This retrospective study revealed that the prevalence of cardiomyopathy in apparently healthy cats was 40.7% (n=24/59), with hypertrophic cardiomyopathy (HCM) (62.5%) as the most common type of cardiomyopathy diagnosed, followed by restrictive cardiomyopathy (RCM) (25.0%), interventricularseptal defect (IVSD) (4.2%), left ventricular outflow tract obstruction (LVOT) (4.2%), and systolic anterior motion (SAM) of the mitral valve (4.2%). The cats’ mean age was 4.9 years old (age range, 7-month-old to 19-year-old). The prevalence was higher in male (45.0%; n=17/38) cats, especially the domestic short hairs (DSH) (46.0%; n=11/24). Among the apparently healthy cats with vertebral heart size (VHS) > 8.0,only 52% (n=12/23) of them were diagnosed with cardiomyopathy. However, 33% (n=12/36) of the cats with normal VHS ≤ 7.9 were diagnosed with heart disease. Consistently, all of the apparently healthy cats with abnormal heart sound were diagnosed with heart disease. About 31.4% (n=16/51) of these cats with normal heart sound had cardiomyopathy too. Occurrence of cardiomyopathy in apparently healthy cats has no association with the patient’s age, sex, and VHS, except for the heart sound. Echocardiography remains the best diagnostic tool, as normal heart size and normal heart sound do not exclude cardiomyopathy in this group of apparently healthy cats.